LITERATUR REVIEW PENGARUH REPUTASI AUDITOR, GOOD CORPORATE GOVERNANCE DAN KOMITE MANAJEMEN RISIKO TERHADAP PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT - Imelda Aryani; Chris Kuntadi (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
This literature review article entitled the influence of auditor reputation, good corporate governance and risk management committee on enterprise risk management disclosure is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research. The method of writing this literature review article is the library research method, which is sourced from Google Scholar online media and other academic online media. The results of this literature review article are that the auditor's reputation has an effect on the disclosure of enterprise risk management, good corporate governance has an effect on the disclosure of enterprise risk management and the risk management committee has an effect on the disclosure of enterprise risk management.